The impact of a commercial lower extremity exoskeleton on metabolic load, perceived exertion, and physiological response to a challenging military relevant task: A randomized cross-over design pilot study - JoEllen M. Sefton; Frances K. Neal; Philip J. Agostinelli; Nicholas C. Bordonie; Phillip E. Whitley; Nathan T. Pickle; Paulien E. Roos (PLoS ONE, 2025)
Purpose To assess physiological metrics during the use of a commercially available bilateral active ankle exoskeleton during a challenging military-relevant task and if use of the exoskeleton during this task influences: metabolic load, physiological measures or rate of perceived exertion. Methods Nine healthy volunteers (5M, 4F) completed this randomized cross-over design trial, with a baseline visit and two randomized test sessions (with/without the exoskeleton). Variables included impact on time to exhaustion during walking on a treadmill at varying speeds and gradients (0–15%) at 26.7°C, 50% humidity with a loaded rucksack (30% body weight). The primary outcome measure was change in metabolic cost with/without the exoskeleton (O2 consumption, metabolic equivalents); secondary outcomes were change in heart rate and perceived exertion between conditions. Results Participants averaged 22.4 ± 4.5 years old, 173.7 ± 7.4 cm tall, weighed 80.9 ± 13.9 kg, and VO2max of 43.8 ± 10.6 mL/kg/min. Total kcals did not differ between conditions (with/without exoskeleton; t = 0.98; p = 0.357). Kcals/min were significantly lower (1.06 kcals/min) with the exoskeleton (t = 3.94; p = 0.004). Average oxygen consumption (VO2) was significantly lower (2.36 mL/kg/min) with the exoskeleton (t = 2.81; p = 0.023), and peak VO2 was 3.33 mL/kg/min lower with the exoskeleton (t = 2.37; p = 0.045). Peak and Average METS were also lower with the exoskeleton by 0.98 (t = 2.61; p = 0.031) and 1.23 (t = 2.39; p = 0.044) respectively. Conclusions Results suggest a powered ankle exoskeleton may decrease energy consumption during military relevant tasks when conducted in a laboratory environment. There may also be physiological benefits such as reduced core temperate and heart rate. Replication of this work in the field environment is warranted.